Sensible leadership human centered, insightful and prudent - Majluf, Nicolás S. 1945-; Abarca Melo, Nureya (Routledge, 2021)
This Leadership book is part of the Human Centered Book Trilogy, the 2021 volumes of the Routledge Human Centered Management HCM Series. HCM books are pioneering transformation from the traditional humans-as-a-resource approach of the industrial past, to the humans at the center management and organizational paradigm of the 21st century. HCM is built on thetalent and wellbeing of people in the workplace driving work engagement, quality standards, high performance and productivity for long-term organizational sustainability in the global VUCA (volatile, uncertain, complex, ambiguous) environment. This book was carefully crafted by recognized human centered scholars emphasizing theneed for a new type of leader responsive to challenges of the knowledge age, global connectivity and instant communications. The book displays a comprehensive framework for the transformation of common individuals into sensible leaders with high capacity to improve organizational culture using Soft Skills to meet critical responsibilities. Sensible leaders are human centered, insightful, prudent, focused on the needs and feelings of followers. They are integral and ethical leaders serving as guides, coaches and mentors, not forcing followers but perceiving clues and responding promptly to solve organizational challenges. They perform honorably in personal and work environments always caring for the common good. This and its two complementary titles Human Centered Organizational Culture: Global Dimensions and Soft Skills for Human Centered Management and Global Sustainability are timely readings for leaders, managers, researchers, acdemics, practitiones, students and the general public working in organizations across industries and sectors wordwide pursuing quality standards, organizational transformation and sustainability.
Keywords: Leadership; Management -- Social aspects; Organizational behavior; Gestion; Aspect social; Comportement organisationnel; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management; Management; Social aspects